Integrasi Pendidikan Humanistik dan Anti Korupsi Dalam Konteks Pendidikan Islam - Rois, Halim; Muhamad Ayul Ginoga (Institut Muslim Cendekia, 2026)
Contemporary Islamic education faces a range of serious challenges, including moral crisis, the widespread practice of corruption, the strengthening of intolerant attitudes, and the weak integration between religious knowledge and social realities. These conditions indicate that education which emphasizes cognitive and normative aspects alone has not been effective in shaping students with strong integrity. Therefore, a more holistic and transformative educational approach is required through the integration of humanistic education and anti-corruption education within the context of Islamic education. This study aims to conceptually examine the integration of humanistic education and anti-corruption education in Islamic education, identify relevant Islamic values as the foundation for this integration, and analyze its implications for the practice and policies of Islamic education at various levels. This study employs a qualitative approach using a library research method. Data were collected through document analysis of books, journal articles, and other relevant scholarly sources, and were analyzed descriptively and analytically. The findings indicate that humanistic values in Islam—such as justice (‘adl), compassion (rahmah), honesty (ṣidq), and trustworthiness (amanah)—are strongly aligned with the principles of anti-corruption education. The integration of these two approaches can be implemented through value-based curriculum development, contextual and reflective learning approaches, educators’ role modeling, and the cultivation of a school or madrasah culture grounded in integrity. The relevance and implementation of this study demonstrate that the integration of humanistic and anti-corruption education contributes to strengthening the role of Islamic education as a means of forming insan kamil—individuals who are humanistic, moderate, and possess strong integrity. These findings are expected to serve as both theoretical and practical references for educators, administrators of Islamic educational institutions, and policymakers in developing Islamic education that is responsive to contemporary moral and social challenges.